EVALUASI STABILITAS LERENG DAN DINDING PADA PELAKSANAAN KONSTRUKSI BANGUNAN PELIMPAH BENDUNGAN JRAGUNG JAWATENGAH - Miftachul Anwar,; Pratikso, Pratikso; Hermin Poedjiastoeti, (Journal of Innovation Research and Knowledge, 2025)
Planning for the construction of the Jragung Dam began in 1976 by the Directorate General of Water Resources through the Pemali Juana River Area Center (BBWS) which will be built in Semarang Regency, Central Java Province. The research and planning of the Jragung Dam that has been carried out includes a feasibility study (FS) studied by Engineering Consultants Inc. (ECI). Denver, Co. USA (1976), Final Design reviewed by P.R.C. Engineering Consultants, Inc. Englewood, Colorado, USA. (1979), Detailed Design was done by (PT. Indra Karya Branch-1 Malang (2015) and Detail Engineering Design (DED) were carried out by PT. Indra Karya (Persero) in 2019. The purpose of this study is to know, evaluate and recommend the design on the slopes and walls of overflow buildings with the geological conditions at the research site, and the analysis is carried out with the help of geo5 v20 software using the Morgentern-price method. Stability analysis is focused on the analysis of slope stability and stability of overflow building walls, Construction engineering modeled with the help of Geo5 v20 software is the reference in this study. The condition of the rocks at the research site is 3 types of units, namely clay units, sandstone units and kollovial soil units. The slope slope is certified design is 1:08, and results in landslides during construction. Slope flattening on the slope of overflow buildings is very necessary so that the implementation of construction can be carried out. Referring to the Central research institute of electric power industry (CIREPI), the classification of rocks is obtained with a unit class D to CL. The slope stability analysis of the certified design received a safety factor (FK) of 1.4 < 1.5 and the stability of the wall obtained a FK of 1.29 < 1.5 safety factors that are less qualified according to SNI 8640:2017 concerning geotechnical design requirements, so it is necessary to make design changes. The design change was made by flattening the slope slope to 1:1, from the change in the slope the analysis was carried out with the stability results of FK 1.61 > 1.5 and on the walls of the overflow building obtained the stability results of FK 1.62 > 1.5 safety factor value was met. Construction engineering on certified designs and design changes in overflow buildings, that is, in locations where there are rocks with D to CL classification unit conditions, cannot be done using a 1:08 slope design, because the condition of rocks with D to CL classification has high weathering. In this study, it is hoped that when designing a slope with the condition of D to CL classification rocks should be done at least at a slope of 1:1, the problem in this study is a reference for designing a slope slope for the future so that it can be applied properly and minimize the occurrence of landslides when construction is carried out.